'Without United States' Trans-Pacific Partnership Agreement and Vietnam's Apparel Industry. Issue 1 (2nd January 2021) - Nguyen, Vy Thi Tuong; Le, Loan Thanh
ABSTRACT: This study investigates the impacts of the 'without-US' Trans-Pacific Partnership (TPP) agreement on Vietnam's apparel industry with two scenarios: (i) the TPP11 without the US and (ii) the likely killed TPP with Vietnam's participation into the alternative free trade agreement (FTA) of the Regional Comprehensive Economic Partnership (RCEP). The impacts are analyzed through two main policies: tariff elimination and rule of origin, by using the ex-ante partial equilibrium model "Global Simulation Analysis of Industry-Level Trade Policy" (GSIM). The result shows that when the US withdraws from the TPP, export value and trade welfare contributed by the Vietnam's apparel industry would remarkably reduce in comparison with the scenario of the full TPP12. However, if Vietnam joins the RCEP, the ability for Vietnam to comply with the origin regulation is quite feasible, which can slightly promote Vietnam's apparel export into this FTA.